Perspectives on climate change adaptation - a cluster analysis of young Germans to develop tailored educational approaches - Wankmüller, Franziska; Loy, Laura S.; Siegmund, Alexander (Journal of environmental psychology, 2025)
Engaging young people in climate change adaptation (CCA) is essential to ensure overall societal participation in this process. However, there is currently a lack of educational programs and participation opportunities around CCA. In this cross-sectional study in Germany (N = 599, 13-20 years old) we aimed to define subgroups of young people's perspectives on CCA. Based on a modified and expanded Theory of Protection Motivation (Rogers, 1983), we developed a measure to capture aspects relevant to CCA, such as adaptive reactions, risk perception, fear, trust in measures and actors in CCA, and maladaptive reactions. These were supplemented by items on respective subjective and objective knowledge. The cluster analysis identified five subgroups, labeled Protectives, Concerned, Passive-Trusting, Paralyzed, and Non-Protectives. Protectives show motivation to participate in CCA, already know more about this topic, and are older on average than other subgroups. A less pronounced motivation to participate in CCA is shown by the male dominated Paralyzed, who are comparatively alarmed but at the same time have less trust in actors or measures. We discuss specific educational approaches for each subgroup, such as the creation of concrete participation opportunities for the Protectives or ways to strengthen trust in measures through experiences of effectiveness for the Paralyzed.
Online verfügbar: 28. Februar 2025, Artikelversion: 10. März 2025
Gesehen am 07.08.2025